Use of the RS-ATL8 NFAT reporter system for diagnosis of hydatid disease - Barwary, Nafal (2018)
Despite major advances in the diagnosis of infections for many pathogenic organisms, there is still a problem obtaining an accurate immunodiagnosis of Echinococcus infection due to its serological cross-reactivity with other species of taeniid cestodes or at higher taxonomic levels. For this reason, there are ongoing efforts to develop a better method for diagnosis of echinococcosis, especially when the parasite has a crucial role in hypersensitivity reactions. Like other helminthic infections, one of the immunological hallmarks is an elevated serum concentration of parasite-specific IgE. Our aim was to assess the use of IgE reporter system as a possible new method for diagnosis Echinococcus spp infection, using RS-ATL8 NFAT Reporter System, which is a humanised rat basophilic leukaemia (RBL) cell line that can be used to detect the presence of specific human IgE directed against Echinococcus allergens and cross-link their receptors, depending on luciferase generation as an indication of presence of parasite-specific IgE, pointing to infection. Towards this goal, we first optimised the use of the humanised RS-ATL8 Reporter System. This was achieved by optimisation of experimental conditions, such as cell density, stimulation time, optimum conditions for sensitising factors and stimulant optimum concentration. Once a robust standard operating procedure had been elaborated, the second goal was to choose a few Echinococcus antigens for the investigation into their immunogenic properties and potential diagnostic value and to express them recombinantly for testing through the RS-ATL8 NFAT Reporter System. The chosen antigens were EF1-alpha, EgAg5, AgB2, Cyclophilin, Eg19, EgTeg, and EgTPx.